Large eddy simulation of a partially pre-vaporized ethanol reacting spray using the multiphase DTF/flamelet model - Hu, Yong; Kai, Reo; Kurose, Ryoichi; Gutheil, Eva; Olguín Astudillo, Hernán Andrés (International journal of multiphase flow, 2020)
Spray reactive flow finds application in various technical devices, and due to the complex nature, their optimization is very challenging, requiring proper modeling of turbulence/chemistry interactions as well as of the contribution from spray evaporation. This work presents a study of sub-grid scale combustion models, where relevant assumptions on multiphase coupling and their effects are analyzed in detail. For this purpose, two different flamelet approaches, i.e. progress variable spray flamelet and multi-regime gas flamelet are examined in an implementation coupled with the dynamic thickened flame model, along with which the impact of inlet inhomogeneities condition and droplet evaporation taking into account internal temperature gradient is also investigated. The numerical evaluation is carried out in large eddy simulations of a benchmark ethanol spray flame with partial pre-vaporization, where an Eulerian-Lagrangian numerical framework is adopted. The analysis demonstrated that the flame dynamics under consideration is governed by a close coupling between spray evaporation, turbulent dispersion and unsteady flame propagation at upstream shear layers. Results show that the spray flamelets built from counterflow partially-premixed spray flames achieved a better agreement with experiments, capturing the flame structure in terms of gas-phase temperature, OH mass fraction as well as spray statistics.
Gesehen am 11.01.2021